Sutureless repair of spontaneous coronary dissection with free wall rupture and cardiac tamponade. Issue 7 (28th January 2019) - Gannon, Michael P.; Graver, L. Michael; Singh, Avneet
Abstract: Left ventricular free wall rupture is a feared complication of acute myocardial infarction typically presenting with cardiogenic shock. We present a case of spontaneous coronary artery dissection with free wall rupture and cardiac tamponade in an uncommon demographic. Friable myocardial tissue frequently precludes suture technique making biological glue repair a suitable option.